LE RÈGNE DE DIEU, PARMI VOUS OU EN VOUS? (Luc 17, 20-21) - Riesenfeld, Harald (Revue biblique, 1991)
Reprise de la discussion et des parallèles grecs profanes. Pour entos le sens de « au milieu de, parmi » — qui n'a été proposé que depuis le XVIIe siècle — n'est en fait attesté nulle part. Le logion discrédite la recherche des signes extérieurs ; c'est dans son intérieur que l'homme possède la faculté de discerner la venue du Règne (ellipse). A reconsideration of the discussion and of the parallels from non-Biblical Greek. As for entos, the sense of "in the midst of, amongst"—which has been urged from the 17th century onwards—is in fact nowhere evident. The logion discredits searching for outward signs; inwardly man has the capability of discerning the coming of the Kingdom (ellipsis).